Pengaruh Lokasi Dan Fasilitas Terhadap Loyalitas Pelanggan (Studi Pada Mooi Caffe Kecamatan Wlingi Kabupaten Blitar) - Widiyastuti, Tetty; Widiantari, Deananda Agusti (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to determine whether location and facilities affect customer loyalty at MOOI Caffe located in Wlingi, Blitar Regency.The results of this research with the t test show that with a significance value of 0.008 which means this value is smaller than 0.05, this shows that H1 is accepted, meaning that location has a significant effect on customer loyalty. The significance value is 0.389 which means that this value is greater than 0.05, so it indicates that H2 is not accepted, meaning that the facility does not have a significant effect on customer loyalty. The significance value is 0.000 which means that this value is smaller than 0.05 then indicates. In testing with F test, the significance value is 0.000 which is less than 0.05 and the calculated F value of 37.844 is greater than F table 3.09, so it shows together the variables of location and facilities affect customer loyalty at MOOI Caffe